Research on the Effect of Olfactory Stimulus Parameters on Awakening Effect of Driving Fatigue - Tang, Bangbei; Cai, Wenjing; Deng, Lingyun; Zhu, Minxing; Chen, Bingyan; Lei, Qing; Chen, Hao; Wu, Yingzhang (2022 6th CAA International Conference on Vehicular Control and Intelligence (CVCI), 2022)
Drivers who drive for a long time and maintain high concentration during driving, drivers are prone to fatigue and lead to traffic accidents. Aiming at this problem, a method based on odor-wake-up fatigue driving is studied to explore the wake-up effect of different types of odors and different concentrations of odors on driving fatigue. In this paper, the E-prime software-controlled olfactory experience tester released different concentrations of mint, lemon, lavender gas; ErgoLab multi-channel physiologist was used to detect and record the changes in physiological characteristic signals such as electrocardiogram signal (ECG), photoelectric volume pulse wave signal (PPG), and respiratory signal (RESP) under odor stimulation. The Stanford Drowsiness Scale was used to obtain the subjective feelings of the participants, and the subjective and objective data analysis was combined to analyze the fatigue wake-up effect of the driver. Through 30 sets of controlled experiments, the effects of three olfactory stimulating gases (peppermint, lemon, lavender) and their concentration changes on driving fatigue were studied, and the results showed that peppermint, lemon and lavender gases all had a wake-up effect on driving fatigue, peppermint ¿ lavender ¿ lemon at the same concentration, and 80% concentration of peppermint gas had the best wake-up effect on driving fatigue.